Laparoscopy in the Surgical Management of the Non-Palpable Testis - Castillo-Ortiz, Javier; Muñiz-Colon, Luis; Escudero, Karina; Perez-Brayfield, Marcos (Frontiers in Pediatrics, 2014)
Introduction: To demonstrate that laparoscopic intervention should be considered as the initial surgical approach in the management of the non-palpable testis. Methods: From 2007 to 2011, 100 testicular units underwent same surgeon laparoscopic management for non−palpable testis (NPT). Diagnostic laparoscopy was performed in all NPT and intra−abdominal testes (IAT) were managed by laparoscopic orchiopexy if low, laparoscopic Fowler−Stephens technique if high, and laparoscopic orchiectomy if atrophic. Percutaneous access to the abdomen was performed in most cases and laparoscopic management was performed with three 5mm ports. We compared patient age, race, pre/post-operative exam, pre-operative work up, and IAT location upon laparoscopic intervention with surgical outcome. Fisher’s exact test for two independent proportions was used for statistical analysis and reported our results. Results: 100 testicular units underwent diagnostic laparoscopy for NPT. All patients were from Puerto Rican descent. 55.0% were found to be intra-abdominal and were subdivided into groups according to surgical intervention. Mean postoperative follow-up was 24 months. Patients 24 months of age or younger undergoing diagnostic laparoscopy for NPT had a statistically significant probability of resulting in successful laparoscopic orchiopexy as opposed to laparoscopic orchiectomy due to an atrophied IAT (n=55 testicular units, p< 0.05). No laparoscopic related complications were reported. Conclusions: Our findings support the use of an initial laparoscopic approach in the NPT as the majority of these patients will have IAT, avoiding unnecessary inguinal and scrotal explorations. We also recommend that patients with IAT should undergo laparoscopic orchiopexy prior to 2 years of age to increase probability of successful management. Further studies focusing in patients with NPT are needed in the future to confirm our findings.